The development of leadership outcome-indicators evaluating the contribution of clinical specialists and advanced practitioners to healthcare: a secondary analysis - HIGGINS, AGNES; BEGLEY, CECILY; ELLIOTT, NAOMI (My University, 2014)
Aims. To report a secondary analysis of data collected from the case study phase of a national study of advanced practitioners and develop leadership outcomes-indicators appropriate for advanced practitioners. Background. In many countries, advanced practitioners in nursing and midwifery have responsibility as leaders for healthcare development, but without having leadership outcome measures available they are unable to demonstrate the results of their activities. In Ireland, a sequential mixed method research study was used to develop a validated tool for the evaluation of clinical specialists and advanced practitioners. Despite strong evidence of leadership activities, few leadership-specific outcomes were generated from the primary analysis. Design. Secondary analysis of a multiple case study dataset. Methods. Dataset comprised twenty-three case studies of advanced practitioner/clinical specialists from 13 sites across each region in Ireland from all divisions of the Nursing Board Register. Data were collected 2008-2010. Data sources included non-participant observation (n=92 hours) of advanced practitioners in practice, interviews with clinicians (n=21), patients (n=20) and directors of nursing/midwifery (n=13) and documents. Analysis focused on leadership outcome-indicator development in line with the National Health Service’s Good Indicators Guide. Results. The four categories of leadership outcomes for advanced practitioner developed were: i) capacity and capability building of multidisciplinary team; ii) measure of esteem; iii) new initiatives for clinical practice and healthcare delivery and iv) clinical practice based on evidence. Conclusions. The proposed set of leadership outcome-indicators derived from a secondary analysis captures the complexity of leadership in practice. They add to existing clinical outcomes measuring advanced practice.
PUBLISHED
Keywords: Leadership outcomes, outcome-indicator development, advanced nurse/midwife practitioner, clinical nurse/midwife specialist, secondary analysis, case study dataset; Leadership outcomes, outcome-indicator development, advanced nurse/midwife practitioner, clinical nurse/midwife specialist, secondary analysis, case study dataset